Inescapable Fibrosis: The Development of Desquamative Interstitial Pneumonia Post-Lung Transplantation Performed for a Patient with Idiopathic Pulmonary Fibrosis - Paul Lilburn; Divya Pillutla; Vanathi Sivasubramaniam; Marshall Plit (Case Reports in Transplantation)
Interstitial lung disease is characterised by a combination of cellular proliferation, inflammation of the interstitium and fibrosis within the alveolar wall. A 58-year-old man was referred for lung transplantation after developing worsening dyspnoea and progressive hypoxaemic respiratory failure from idiopathic pulmonary fibrosis. Three years later, he developed desquamative interstitial pneumonia in his transplanted lungs, and despite augmentation of immune suppression, he had a progressive decline in his lung function and exercise capacity. Interestingly, in our case, the histopathology obtained post transplant strongly goes against the recurrence of usual interstitial pneumonia/idiopathic pulmonary fibrosis; rather, two separate interstitial disease processes have been identified.